THE PSYCHOLOGICAL ASPECTS OF INDIVIDUAL TRAINING IN THE LIGHT OF QURANIC TEACHINGS - Tayyaba Andleeb (Journal of Religion and Society, 2024)
This study explores the profound psychological dimensions of individual training as guided by the Quran. Rooted in divine wisdom, the Quran provides comprehensive principles for self-discipline and personality development, fostering emotional stability, mental resilience, and spiritual tranquillity. The research emphasizes three critical aspects: self-accountability, patience and gratitude, and balance and moderation. Each element contributes significantly to an individual’s psychological well-being and overall personal growth. The concept of self-accountability, as derived from Surah Al-Hashr (59:18), encourages believers to evaluate their actions and plan consciously for their future. This practice enhances self-awareness, promotes introspection, and empowers individuals to align their behaviors with ethical and moral standards. Furthermore, the Quran underscores the virtues of patience and gratitude in Surah Al-Baqarah (2:153) and Surah Ibrahim (14:7), respectively. Patience helps in coping with adversity, while gratitude fosters a positive outlook on life, reducing stress and emotional burdens. The principle of balance and moderation, highlighted in Surah Al-Furqan (25:67), calls for a harmonious approach to all aspects of life. This teaching prevents extremes, ensuring emotional stability and protecting individuals from the negative impacts of excessive indulgence or deprivation. Additionally, the Quran’s emphasis on remembrance of Allah, as illustrated in Surah Ar-Ra'd (13:28), promotes spiritual well-being, which is intrinsically linked to psychological peace. Such practices reduce anxiety, instill hope, and build inner strength. By drawing parallels between Quranic principles and modern psychological frameworks, this research demonstrates the Quran’s timeless relevance in addressing contemporary psychological challenges. The integration of Quranic guidance in personal development strategies offers practical solutions for mental health issues such as stress, depression, and emotional instability. The findings advocate for the incorporation of these divine teachings into counseling and therapy, highlighting their potential to cultivate resilience, self-regulation, and a fulfilling life. In conclusion, the Quran provides a holistic framework for individual training, emphasizing the interconnection between spiritual, emotional, and psychological dimensions. Its principles not only nurture a balanced and peaceful life but also equip individuals to face modern challenges with confidence and faith. Keywords: Psychological Aspects, Individual Training, Quranic Teachings, Spiritual Well-Being